PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM PAIR SOLO BERBANTUAN SOFTWARE GEOGEBRA UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI LINGKARAN - Laamena, Christina M; Gaspersz, Magy; Tupamahu, Pieter Z (Jurnal Magister Pendidikan Matematika (JUMADIKA), 2019)
This study aims to improve the learning outcomes of grade VII students of SMP Negeri 6 Ambon in circle material by using the Team Pair Solo type cooperative model with the help of the Geogebra Software. The subjects of this study were students of class VIII-Science of SMP Negeri 6 Ambon, amounting to 28 students. This type of research was Classroom Action Research (CAR). This study was conducted in two cycles with every cycles suddenly from four meetings. Data in this study were collected through observation and test sheets. The findings in this study indicate that the final test results from cycle I to cycle II increased by 25%. Based on the results of this study it can be concluded that student learning outcomes in circle material can be improved with Team Pair Solo learning models assisted by Software Geogebra Software in class VIII of SMP Negeri 6 Ambon